Bauhinia purpurea leaves' extracts exhibited in vitro antiproliferative and antioxidant activities - Zakaria, Zainul Amiruddin; Rofiee, Mohd Salleh; Teh, Lay Kek; Salleh, Mohd Zaki; Sulaiman, Mohd Roslan; Abdullah, Muhammad Nazrul Hakim (Academic Journals, 2011)
The antiproliferative and antioxidant activities of various extracts of the leaves ofBauhinia purpurea were studied using in vitro standard assays. The aqueous and chloroform extracts successfully inhibited the proliferation of all cancer cells while the methanol extract inhibited the proliferation of all cells except the CEMss cells when assessed using the 3,(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide) (MTT) assay. The aqueous extract was effective against MCF-7 (IC50 ≈ 9µg/ml), MDA-MB 231 (IC50 ≈ 17 µg/ml) and Caov-3 (IC50 ≈ 16 µg/ml); the chloroform extract was highly effective against the CEMss (IC50 ≈ 18 µg/ml) and HeLa (IC50 ≈ 21 µg/ml); and the methanol extract was highly effective only against the HL-60 (≈ 12 µg/ml) cell lines. Interestingly, all extracts did not inhibit the proliferation of 3T3 cells suggesting their non-cytotoxic properties. The aqueous and methanol, but not chloroform, extracts of B. purpurea (20, 100 and 500 mg/ml) exhibited concentration-dependent antioxidant activity only in the superoxide scavenging assay, but low to moderate activity in the 2,2-diphenyl-1-picrylhydrazyl (DPPH) radical scavenging assay, which could be associated with their total phenolic contents. In conclusion, the B. purpurea leaf possesses potential antiproliferative and concentration-dependent antioxidant activities. Purification and determination of active compounds are required for further study.